![image](https://tex.z-dn.net/?f=%28x%2B9%29%28x%2B1%29%28x-11%29%3E0%5C%5C%28x%2B9%29%28x%2B1%29%28x-11%29%3D0%5C%5Cx%3D-9%2C%5C%3Bx%3D-1%2C%5C%3Bx%3D11%5C%5C%5C%5Cx%5Cin%28-%5Cinfty%3B%5C%3B-9%29%5C%5Cx%3D-10%5CRightarrow%28x%2B9%29%28x%2B1%29%28x-11%29%3D%28-10%2B9%29%28-10%2B1%29%28-10-11%29%3D%5C%5C%28-1%29%5Ccdot%28-9%29%5Ccdot%28-21%29%3D-189%3C0%5C%5C%5C%5Cx%5Cin%28-9%3B%5C%3B-1%29%5C%5Cx%3D-2%5CRightarrow%28x%2B9%29%28x%2B1%29%28x-11%29%3D%28-2%2B9%29%28-2%2B1%29%28-2-11%29%3D%5C%5C%3D7%5Ccdot%28-1%29%5Ccdot%28-13%29%3D91%3E0%5C%5C%5C%5Cx%5Cin%28-1%3B%5C%3B11%29%5C%5Cx%3D0%5CRightarrow%28x%2B9%29%28x%2B1%29%28x-11%29%3D%280%2B9%29%280%2B1%29%280-11%29%3D%5C%5C%3D9%5Ccdot1%5Ccdot%28-11%29%3D-99%3C0%5C%5C%5C%5Cx%5Cin%2811%3B%5C%3B%2B%5Cinfty%29%5C%5Cx%3D12%5CRightarrow%28x%2B9%29%28x%2B1%29%28x-11%29%3D%2812%2B9%29%2812%2B1%29%2812-11%29%3D%5C%5C%3D21%5Ccdot13%5Ccdot1%3D273%3E0%5C%5C%5C%5Cx%5Cin%28-9%3B%5C%3B-1%29%5Ccup%2811%3B%5C%3B%2B%5Cinfty%29)
0\\(x+9)(x+1)(x-11)=0\\x=-9,\;x=-1,\;x=11\\\\x\in(-\infty;\;-9)\\x=-10\Rightarrow(x+9)(x+1)(x-11)=(-10+9)(-10+1)(-10-11)=\\(-1)\cdot(-9)\cdot(-21)=-189<0\\\\x\in(-9;\;-1)\\x=-2\Rightarrow(x+9)(x+1)(x-11)=(-2+9)(-2+1)(-2-11)=\\=7\cdot(-1)\cdot(-13)=91>0\\\\x\in(-1;\;11)\\x=0\Rightarrow(x+9)(x+1)(x-11)=(0+9)(0+1)(0-11)=\\=9\cdot1\cdot(-11)=-99<0\\\\x\in(11;\;+\infty)\\x=12\Rightarrow(x+9)(x+1)(x-11)=(12+9)(12+1)(12-11)=\\=21\cdot13\cdot1=273>0\\\\x\in(-9;\;-1)\cup(11;\;+\infty)" alt="(x+9)(x+1)(x-11)>0\\(x+9)(x+1)(x-11)=0\\x=-9,\;x=-1,\;x=11\\\\x\in(-\infty;\;-9)\\x=-10\Rightarrow(x+9)(x+1)(x-11)=(-10+9)(-10+1)(-10-11)=\\(-1)\cdot(-9)\cdot(-21)=-189<0\\\\x\in(-9;\;-1)\\x=-2\Rightarrow(x+9)(x+1)(x-11)=(-2+9)(-2+1)(-2-11)=\\=7\cdot(-1)\cdot(-13)=91>0\\\\x\in(-1;\;11)\\x=0\Rightarrow(x+9)(x+1)(x-11)=(0+9)(0+1)(0-11)=\\=9\cdot1\cdot(-11)=-99<0\\\\x\in(11;\;+\infty)\\x=12\Rightarrow(x+9)(x+1)(x-11)=(12+9)(12+1)(12-11)=\\=21\cdot13\cdot1=273>0\\\\x\in(-9;\;-1)\cup(11;\;+\infty)" align="absmiddle" class="latex-formula">